Analisis Pelatihan, Disiplin Kerja, Remunerasi, dan Motivasi Berprestasi dengan Kepuasan Kerja Sebagai Variabel Intervening terhadap Kinerja Karyawan - Abd Rasyid Syamsuri; Zulkifli Musannip Efendi Siregar (JSHP : Jurnal Sosial Humaniora dan Pendidikan, 2018)
This study aims to analyze the training, work discipline, remuneration, achievement motivation with job satisfaction as an intervening variable on employee performance. Research respondents are the employees PT. Plantation Milano Panai Tengah Labuhanbatu of 61 respondents with sampling using slovin formula. Sources and data collection techniques used in this study are primary data, to wit data obtained or collected directly from the source data through interviews and a list of questions given to the respondents. The data analysis technique used SEM (Stuctural Equation Modeling) with SmartPLS program. R square value is known that job satisfaction variable and employee performance can be explained by training variables, work discipline, remuneration and achievement motivation equal to 67,8%, and 61,2%. The result of Path Coefficients with Statistics (O / STDEV) used to examine the analysis of training, work discipline, remuneration, achievement motivation on employee performance with job satisfaction as intervening variable. The results showed that the training had positive and insignificant effect on job satisfaction. Discipline has positive and insignificant effect on job satisfaction. Remuneration has a positive and insignificant effect on job satisfaction. Achievement motivation has a positive and significant impact on job satisfaction. Training has a positive and insignificant effect on employee performance. Achievement motivation has positive and insignificant effect on employee performance and job satisfaction have positive and significant effect to employee performance.